The Implementation of Assessments Based on Merdeka Curriculum in Teaching Writing at Phase E - Iman Asrori, Chandra; Susanti, Yunik; DewiKencanawati (LPPM Universitas Advent Indonesia, 2025)
English learning in Merdeka Curriculum provides opportunities for students to communicate with global citizens from different cultural backgrounds. By mastering English, students will have greater opportunities to interact using a variety of texts. Phases E and F of English learning focus on strengthening oral and written language skills, targeting CEFR B1 proficiency. Descriptive text is chosen for written language because students often struggle with it in high school. Therefore, assessment that refers to the process and assessment standards is needed to determine if students have effectively and efficiently achieved the learning objectives. Merdeka Curriculum prioritizes formative assessment. This study aims to describe the process of implementing the assessment and identify its strengths and challenges. This study uses a qualitative research approach with case studies. The subjects of the study are an English teacher, Mr.S, and one class, X-1, of 34 students at SMAN 6 Kediri. Data sources include the English teacher and the teaching-learning process. Data validity uses technique triangulation. The findings on the assessment process include planning and implementation. For planning, the teacher creates teaching material, teaching module, teaching support tool. For implementation, formative assessments, including diagnostics, practice, discussion, written tests, and reflection sections, are carried out as intended, but summative assessment, a written test section, is not. Strengths include the implementation of different types of assessments, achievement of Pancasila student profile, and achievement of English learning outcomes in writing and presenting elements at Phase E. Challenges include inappropriate time allocation, inappropriate assessments, and insufficient student understanding.